2004
DOI: 10.2193/0022-541x(2004)068[0120:rdobdi]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Recruitment Dynamics of Black-Tailed Deer in the Western Cascades

Abstract: We used cohort analysis to reconstruct a Columbian black‐tailed deer (Odocoileus hemionus columbianus) population from 1979 to 1999 in the western Cascade Range, Washington, USA. We used reconstructed population estimates and age‐class representations to analyze relationships among fawn recruitment, deer density, forage availability, and weather influences during the fawning period. Fawn recruitment was found to be significantly correlated with deer density the previous year as well as available forage in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
3

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 32 publications
0
31
3
Order By: Relevance
“…If nutritional condition represents the relative position of the population with respect to K (Piasecke and Bender ), then that position would be expected to be partially reflected in the following year. Time lags and carryover effects in response to resource limitation are becoming increasingly recognized as influential factors in the regulation of ungulate populations (Fryxell , Gilbert and Raedeke , Keyser et al , Monteith et al , Harrison et al ), and stress the importance of not considering a particular season or year in isolation (Kie et al , Monteith et al ).…”
Section: Discussionmentioning
confidence: 99%
“…If nutritional condition represents the relative position of the population with respect to K (Piasecke and Bender ), then that position would be expected to be partially reflected in the following year. Time lags and carryover effects in response to resource limitation are becoming increasingly recognized as influential factors in the regulation of ungulate populations (Fryxell , Gilbert and Raedeke , Keyser et al , Monteith et al , Harrison et al ), and stress the importance of not considering a particular season or year in isolation (Kie et al , Monteith et al ).…”
Section: Discussionmentioning
confidence: 99%
“…Across each summer range, we calculated the mean minimum temperature in June (°C), total precipitation in June (cm), cumulative average precipitation from May through September (cm), and the average maximum temperature from June through August (°C). June is the month that fawns are born, and we suspected that their survival may be reduced by cold, wet weather (Gilbert & Raedeke, ). Meanwhile, summer precipitation has been correlated with forage quality (Blanchard et al ., ), increased recruitment (Hurley et al ., ), and maternal condition in ungulates (Cook et al ., ), while high summer temperatures have been associated with smaller litter sizes (Monteith et al ., ) and reduced recruitment (Monteith et al ., ).…”
Section: Methodsmentioning
confidence: 99%
“…Early-life survival is very sensitive to climatic conditions (Gilbert and Raedeke 2004;Jones et al 2005); hypothermia has been shown to be one of the most important causes of fawn mortality in the absence of predators (Andersen and Linnell 1998;Olson et al 2005). In particular, the period shortly after birth is critical due to limited energy reserves and the small body size of fawns [reviewed for lambs (Ovis aries) by Nowak and Poindron (2006)].…”
Section: Introductionmentioning
confidence: 99%